Influência do regime ondulatório sobre "sea wall" de proteção na praia de Iparana - Caucaia - Ceará - Brasil - Dias, Nilena Brito Maciel (2005)
Coastal environments of northeastern Brazil have suffered considerable environmental degradation, caused by the growing impact of human activities on natural resources. In recent years, there has been a continuous process of erosion on the beach Iparana, in the municipality of Caucaia, metropolitan region of Fortaleza. This erosion is receding shoreline, sandstone exposure and dune removal. On the coast of Fortaleza and adjacent municipalities, the occupation of coastal areas has promoted changes in the environment, so their status is very important to understand the process that occurs in Iparana area. For this research were obtained data related to the wave regime, tides and winds occurring in the region, as well as photographic surveys and topographic sections of "sea wall" in the study. In this paper a monthly monitoring of the behavior of the "sea wall" over a year. It sought to develop comparative studies between various surveys of beach profiles in order to assess their conditions of stability and possible changes in the dynamic equilibrium of the beach. Observing the sections made along the entire wall, it may be noted that there was a normal map. Also, we saw that this coastal strip, despite the intense erosion, the "sea wall" has been able to control erosion, preventing it from spreading toward the cotinente.